Multiple Optical Frequency Conversions in Few‐Layer GaSe Assisted by a Photonic Crystal Cavity. Issue 22 (5th September 2018) - Fang, Liang; Yuan, Qingchen; Fang, Hanlin; Gan, Xuetao; Li, Juntao; Wang, Tao; Zhao, Qinghua; Jie, Wanqi; Zhao, Jianlin
Abstract: While 2D materials have intriguing second‐order nonlinearities with ultrahigh coefficient and electrical tunability, their atomic layer thicknesses hinder explorations of other optical frequency conversions (OFCs) than second harmonic generation (SHG) due to inefficient light‐coupling and unachievable phase‐matching. By resonantly pumping a photonic crystal cavity integrated with a few‐layer GaSe, it is reported that it is possible to realize multiple second‐order nonlinear processes in GaSe even with microwatts continuous wave pumps, including SHGs, sum‐frequency generations (SFGs), cascaded SFGs, and their induced third harmonic generations. These OFCs arise from the significant cavity‐enhancements. The enhancement factor of an SHG process is estimated exceeding 1300. The cascaded SFGs have comparably strong intensities with those of SHGs. To the best of our knowledge, this is the first observation of cascaded second‐order nonlinear processes in 2D materials. The cavity‐assisted OFCs can provide a view to study deterministic OFCs in 2D materials with low pump power and expand their optoelectronic applications to nonlinear regime. Abstract : Microwatts continuous‐wave pumped multiple second‐order nonlinear processes in 2D GaSe are realized with the assistance of strongly localized resonant modes in a photonic crystal nanocavity, including second harmonic generations, sum‐frequency generations (SFGs), cascaded SFGs, and their induced third harmonic generations.